Answers

2016-03-16T14:08:21+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(a+b)^3=a^3+b^3+3ab(a+b)
there is no formulas for a^2+b^2
2 1 2
The Brainliest Answer!
2016-03-20T17:46:59+05:30

1. (a + b)³ = a³ + b³ + 3ab(a + b)

We Can Derive it by = 

(a + b)³ = (a + b) (a + b)  (a + b)
             = (a² + b² + 2ab) (a + b)
             = a³ + b³ + 2a²b + 2ab² + a²b + ab²
             = a³ + b³ + 3a²b + 3ab²
             = a³ + b³ + 3ab(a + b) -------[Taking 3ab Common]

2. a² + b² = [ There is No Formula For It but There is Formula for ] 
The Following 


3. a² - b² = (a + b) (a - b)
4. (a + b)²= (a² + b² + 2ab)

Hope U Understood
I Know i Was Late But
Mark This Brainliest if This Helped You
Thankx
2 5 2
Thankx
ur welcome nyc answering
Thankx Once Again
ur welcome once again
Hmmm